PENGARUH FORMALISASI PENGEMBANGAN SISTEM, PARTISIPASI PEMAKAI, DAN KOMPLEKSITAS TUGAS TERHADAP EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI PADA KOPERASI SERBA USAHA DI KECAMATAN KINTAMANI, BANGLI - Ria Juliastini; Sang Ayu Putu Arie Indraswarawati; I Putu Fery Karyada (UNHI Press, 2020)
The purpose of this study was to determine the effect of formalizing system development, user participation, and task complexity on the effectiveness of the use of accounting information systems in Multipurpose Cooperatives in Kintamani District, Bangli. The population used in this study were all employees of the Multipurpose Cooperative in Kintamani District, Bangli as many as 171 people. Determination of the sample using purposive sampling to obtain 90 people as samples. Performed data analysis using multiple linear regression analysis, determination, t test, and F test. The results of the analysis showed that formalizing the system development of the effectiveness of applying accounting information systems obtained a regression coefficient of 0.381, the value of t calculate 2,632 and the t-test significant value of 0.010 <0.05, so that H1 is accepted. The influence of user participation on the effectiveness of the application of accounting information systems obtained a regression coefficient of 0.930, a calculated t value of 9.067 and a significant value of t test of 0.000 <0.05, so that H2 is accepted. The effect of task complexity on the effectiveness of applying the accounting information system obtained a regression coefficient of -0.332, a calculated value of -3.024 and a significant value of t test of 0.003 <0.05, so that H3 was accepted.